Standardization of Genomic DNA Isolation Method from Mature Leaves and SSR-PCR Conditions for Flemingia semialata an Alternative Lac Host Plant - Kumar, Aditya; Kumari, Khushboo (Indian Forester, 2023)
Flemingia is an important multipurpose leguminous perennial shrub, grows from 0.5 to 2.5 meters and sometimes upto 3 meters. It is one of the most suitable plant species for kusumi lac strain which produces best quality lac in the world. To develop improved and productive varieties of Flemingia spp., it was needed to know the genetic diversity present in the germplasm and breeding material. Molecular markers are best tool to study the genetic diversity present in breeding population and to utilize molecular markers, genomic DNA of high quality and quantity was required. To obtain high quality and quantity of genomic DNA at lesser cost, it was needed to standardize a robust genomic DNA isolation protocol. Therefore, in the present study, the DNA isolation protocol of Murray and Thompson (1980) was modified and optimized. The standardized protocol yielded 1200-1500 ng/Âµl genomic DNAwith an average of 1359 ng/Âµl DNA from 40 samples of F. semialata and F. macrophylla. A very low level of RNA, protein, phenolics and polysaccharide contaminants were recorded (A260/A280 ratio ranges from 1.8-1.85) from the isolated DNA. The isolated DNA was utilized for molecular characterization and genetic diversity assessment of Flemingia semialata and Flemingia macrophylla by using microsatellite markers. The standardized protocol was yielded genomic DNA of good quality and quantity from both, juvenile leaf and matured leaf samples. The optimized protocol was also utilized for the genomic DNA isolation of Shorea robusta and Buchanania cochinchinensis.